CRISIS SITUATIONS IN TOURIST DESTINATIONS: HOW CAN THEY BE MANAGED? - Alfonso Vargas-Sánchez (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2018)
Crisis management in tourism, whether due to natural catastrophes or to any other reason, acquires particular relevance because tourist centres are usually located in places (coasts / beaches, wooded areas, mountains, valleys of rivers,...) whose characteristics rise the potential risk, to which it is necessary to join the high densities of population if the event that triggers it (fire, torrential rain,...) takes place in periods of maximum affluence (high season). In addition, tourists are more vulnerable than residents, because of its lack of familiarity with the area and, in the case of international tourism, due to the limitations of not speaking / mastering the local language. If tourists become victims of a disaster of this type, with the added risk caused by overcrowding, the negative impact on the destination image multiplies.Although tourism has proven to be a highly resilient activity, recovering in a relatively short time from the negative impacts of this type of events, it is no less true that managers of tourist business and destinations should not underestimate their effects.Within this framework, and without prejudice the fact that each case is unique and therefore cannot be separated from its context, the aim of this paper is to synthesize a series of proposals that the scientific literatura has revealed, as general guidelines to take into account for a proactive management of crisis situations in a tourist destination, overcoming an approach to them based on a mere reactive response.